PENERAPAN METODE QOWAID WA TARJAMAH UNTUK MENINGKATKAN MOTIVASI DAN PRESTASI BELAJAR BAHASA ARAB SISWA KELAS X SEMESTER GENAP SMA AL-KAUTSAR BANDAR LAMPUNG : PENERAPAN METODE QOWAID WA TARJAMAH - Muhammad Singgih (An Naba, 2018)
Language is a communication tool to interact with the environment. In general education institutions, especially at the junior and senior high school levels, Arabic has become the main choice of teaching foreign languages ​​besides English. Submission of Arabic material properly must be supported by appropriate methods for accelerating the mastery of Arabic by students. The problem in this study is (1) how do students respond to the use of the Qowaid wa tarjamah / grammar and translate method)? (2) how the effect of student learning activities using these methods on students' Arabic learning motivation and achievement. The purpose of this study is to describe the application of Qowaid wa tarjamah / grammar and translate in Arabic learning, as well as its influence in increasing students' motivation and learning achievement in Arabic. The data source in this study were the results of student learning tests for classes X.2 and X.7 in Al-Kautsar Bandar Lampung High School in the 2008/2009 academic year as a control class by using descriptive research methods. While the data collection techniques are through questionnaires and tests, essay tests and multiple choice. With Qowaid wa tarjamah / grammar and translate method increases 24.42% in test questions about the vocabulary structure. While translating test questions increased by 20.53%. Learning motivation is quite good, there are 83.25% of students who like learning Arabic. From the above analysis the researchers concluded the cause of increased motivation and achievement of students' Arabic lessons depends on the methods used by the teacher in the learning process both in sentence structure, vocabulary, and learning motivation.